Pseudofilamentous desmids (Zygnematophyceae) from an Amazonian floodplain lake (Macapá, AP, Brazil) - de Araújo, Camila Barbosa; Bicudo, Carlos Eduardo de Mattos; Takiyama, Luís Roberto; de Melo, Sérgio (Iheringia, Série Botânica., 2020)
The aim of this study was to conduct a floristic inventory and taxonomical characterization of the pseudofilamentous desmids from a floodplain lake in the Oriental Amazon, Northern Brazil. Twenty-one taxa were identified and described. Desmidium quadratum var. constrictum Nordstedt, Haplozyga armata var. armata (Nordstedt) Raciborski, and Spondylosium rectangulare var. goyazense Förster were registered for the first time for the Amazon region. Desmidium longatum Wolle, has only been recorded previously in North America and is now registered for the first time in Brazil. According to their frequency of occurrence during the study period, 10 taxa were considered frequent, nine were less frequent, and two were considered rare. Most taxa were collected during both the rainy and the dry (less rainy) seasons, whereas six taxa were exclusively found during the rainy period.